Beneficial effects of oral administrations of grape seed extract on healing of surgically induced skin wounds in rabbits - Sagliyan, A.; Benzer, E.; Kandemir, F. M.; Gunay, C.; Han, M. C.; Ozkaraca, M. (Ecole Nationale Veterinaire Toulouse, 2012)
This study examined the effects of orally given grape seed extract (GSE) on healing of surgically induced full thickness skin wounds in terms of clinical, histopathological and biochemical aspects. A total of 48 healthy. adult male New Zealand rabbits were randomly divided in 2 equal experimental and control groups: one week prior the surgery, 260 mg/kg grape seed extract was orally given for 20 days to the assay animals. A circular full thickness skin wound (2.5 cm in diameter) was made in the back midline of all rabbits under anaesthesia then, macroscopic and histopathological aspects as well as the tissue oxidant/antioxidant balance were determined on 6 rabbits from each group slaughtered at the 5th, 10th, 15th and 20th days post-surgery. In treated rabbits, it was clinically observed that the wound contraction was significantly amplified and the histological processes of re-epithelisation, granulation tissue development, collagen accumulation and angiogenesis were markedly hastened whereas the inflammatory reaction and the ulcer disappeared more rapidly than in the not-treated controls. Furthermore, the maximal skin MDA formation observed on the 10th day was significantly depressed and the antioxidant catalase (CAT) and glutathione peroxidase (GSH-Px) activities remained significantly elevated until the 15th day compared to the controls. These results demonstrate the beneficial effects of treatment with GSE on skin wound healing in rabbits.
Keywords: Surgical excision wound; skin; rabbit; grape seed extract; wound healing; histopathological criteria; oxidative stress; antioxidants